First Post-Legislative Scrutiny in Georgia: Steps Towards Generating Result-oriented Laws - Kakhaber Kuchava (Journal of Southeast Asian Human Rights, 2019)
The effective implementation of law is a complex process. This process depends on the availability of human resources, public engagement, funding (at least, on the stage of piloting), among others. Often, the focus is on getting legislation adopted, rather than on practical implementation and its impact. To fill in this gap, oversight over the Implementation of Normative Acts (i.e., Post-legislative scrutiny, hereinafter “PLS”) has been introduced in the Rules of Procedures of the Parliament of Georgia (hereinafter, the “Parliament”). This article scrutinises the procedures that are shaping the Parliament’s ability to conduct PLS as well as its interaction with the executive. The working theory for this paper is that insufficient attention has been paid to the review of legislation after its enactment in Georgia. The paper addresses the work that has been undertaken at the national level, particularly through monitoring the effects of adopted legislation in ensuring benefits for constituents in the ways initially intended. Furthermore, it will reflect on the challenges identified in the ongoing PLS process by the Environments Protection and Natural Resources Committee (hereinafter “Environment Committee”) and the lessons learned based on the experience. The article uses a case study of Georgia to explore the context and challenges for effective PLS. For comparision, this research adopted the UK approach, where it is common to review the laws three to five years after enactment.